PENGARUH PROMOSI DAN BIAYA KULIAH TERHADAP KEPUTUSAN KULIAH DI PERGURUAN TINGGI ISLAM - Suci Mahabbati; Elex Sarmigi; Marda Tila (Al Dzahab, 2024)
Purpose: This study was conducted to examine whether promotion and tuition fees influence students’ decisions to choose Islamic higher education institutions in Kerinci Regency and Sungai Penuh City. Design/Methodology/Approach: The sample of this study consisted of 227 respondents. Data were collected using questionnaires. Data analysis was performed using multiple linear regression analysis. Findings: The results indicate that promotion has a positive and significant effect on students’ decisions in choosing higher education institutions. Tuition fees also have a positive and significant effect on decision-making. Simultaneously, promotion and tuition fees significantly influence students’ decisions in selecting higher education institutions. Research Implications: The findings provide practical implications for higher education administrators in designing more effective promotional strategies and establishing competitive and affordable tuition fee policies to enhance institutional attractiveness and increase prospective student interest.